The Role of Bureaucratic Behavior on Increasing The Effectiveness of Educational Policies : Perspective of Robbin's Theory Development - Yacob Noho Nani; Rustam Tohopi; Fenti Prihatini Tui; Juriko Abdussamad (Sawala : Jurnal Administrasi Negara, 2022)
The concern for the implementation of national education is the decline in the competitiveness of national education. Although the Human Development Index has increased nationally, when compared to ASEAN countries and globally. According to the Central Statistics Agency (BPS) in 2020, Indonesia is ranked 6th in ASEAN and 111th out of 186 countries (UNDP, 2019). Indonesian education is in a position below Singapore, Brunei Darussalam, Malaysia, Thailand and the Philippines. Therefore, the purpose of this research is to examine the role of bureaucratic behavior on the effectiveness of policies to expand access to education evenly in the perspective of Robbins' theory development. The research method is a case approach with qualitative analysis using semi-structured interviews, focus group discussions (FGD) and documentary reviews as data collection instruments. Altogether, 45 in-depth interviews. .The results show that behavioral analysis at the individual, group and organizational levels as stated by Robbins (2010) has implications for increasing effectiveness through increasing employee motivation, job satisfaction, cooperation, public involvement in the education sector. However, it cannot describe how to deal with paternalism, behavioral deviations, bureaucratic swelling and so on, in a concrete way. As the findings of the study, it was determined "Patterns of behavioral relationships" as a novelty of organizational behavior analysis with implications for improving behavioral tendencies as a driving and inhibiting factor for the success of the expansion and equity of education. Behavioral relationship patterns can also moderate behavioral elements in increasing effectiveness.